The SKI proto-oncogene enhances the in vivo repopulation of hematopoietic stem cells and causes myeloproliferative disease - Sofie Singbrant; Meaghan Wall; Jennifer Moody; Göran Karlsson; Alistair M. Chalk; Brian Liddicoat; Megan R. Russell; Carl R. Walkley; Stefan Karlsson (Haematologica, 2014)
The proto-oncogene SKI is highly expressed in human myeloid leukemia and also in murine hematopoietic stem cells. However, its operative relevance in these cells remains elusive. We have over-expressed SKI to define its intrinsic role in hematopoiesis and myeloid neoplasms, which resulted in a robust competitive advantage upon transplantation, a complete dominance of the stem and progenitor compartments, and a marked enhancement of myeloid differentiation at the expense of other lineages. Accordingly, enforced expression of SKI induced a gene signature associated with hematopoietic stem cells and myeloid differentiation, as well as hepatocyte growth factor signaling. Here we demonstrate that, in contrast to what has generally been assumed, the significant impact of SKI on hematopoiesis is independent of its ability to inhibit TGF-beta signaling. Instead, myeloid progenitors expressing SKI are partially dependent on functional hepatocyte growth factor signaling. Collectively our results demonstrate that SKI is an important regulator of hematopoietic stem cell activity and its overexpression leads to myeloproliferative disease.